FRI0394 The Proteasome Inhibitor Bortezomib Ameliorates Refractory Systemic Lupus Erythematosus (SLE): A Prospective Multi-Centre Observational Study. (10th June 2014) - Alexander, T.; Sarfert, R.; Klotsche, J.; Rubbert-Roth, A.; Lorenz, H.-M.; Rech, J.; Hoyer, B.; Cheng, Q.; Waka, A.; Taddeo, A.; Kühl, A.A.; Schett, G.; et al.
Abstract : Objectives: The proteasome inhibitor bortezomib, approved for the therapy of multiple myeloma, depletes plasma cells (PCs) and ameliorates nephritis in mouse models of systemic lupus erythematosus (SLE). Here, we analyzed the efficacy of bortezomib as induction therapy in patients with refractory SLE. Methods: Twelve patients with active SLE were included in this prospective multicentre cohort study. The patients received one to four cycles of intravenous bortezomib (Velcade®) 1.3mg/m 2 as "off-label" treatment. Disease activity was evaluated using the SELENA-SLEDAI score. We determined serum concentrations of anti–double-stranded DNA (anti-dsDNA) and protective antibodies. Multicolor flow cytometry was performed to analyze peripheral blood B and PC subsets as well as Siglec-1 expression on monocytes as surrogate marker for type I interferon (IFN) activity. Results: The disease activity significantly decreased upon induction therapy with bortezomib and remained stable for the following 3 months under maintenance therapies. Treatment-related adverse events were mild or moderate. During proteasome inhibition, serum antibody concentrations significantly declined with greater reductions in anti-dsDNA (∼60%) than protective (∼30%) antibodies. Upon bortezomib treatment, numbers of HLA-DR + short-lived (p=0.024) and HLA-DR – long-lived (p=0.038) peripheral blood PCs were strongly decreased, whereas circulating B cells remained virtually unaffected. Notably, PC numbers significantly increased in-between cycles. Siglec-1 expression on monocytes significantly declined (p<0.001) indicating reduced type 1 IFN activity. Conclusions: Bortezomib targeting PCs and type I IFN activation may represent an effective treatment option with rather low toxicity in refractory SLE patients. Bortezomib efficiently induces short-term remissions but requires maintenance treatment inhibiting PC regeneration for sustained efficacy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5884